SÍNDROME DE DESGASTE PROFESIONAL, ÍNDICE DE MASA CORPORAL Y OTROS FACTORES ASOCIADOS A LOS PROFESORES DE EDUCACIÓN FÍSICA DE LAS INSTITUCIONES EDUCATIVAS DE IBAGUÉ (Fiep Bulletin - online, 2016)
This article aims to show the progress of an ongoing investigation whose purpose is to determine the levels of professional burnout syndrome (SDP) or also called Burnout, Work (SQT) of physical education teachers and the relationship BMI between variables, sex and age for each of the dimensions of this syndrome (Illusion for work, psychological exhaustion, Indolence and Guilt). It is a study of descriptive and correlational, where applied instrument called "Questionnaire for Assessing Burn Syndrome Working with Professional version Educación.CESQT-PE", evaluated each of the dimensions of the syndrome. As for the BMI, body weight and height within the parameters established by the ISAK was taken. As a result we expect to find high levels of SDP, and meaningful relationships between BMI, sex and age.
Keywords: Professional Burnout Syndrome; Physical Education Teacher.